Optimization of Initial Folding Square Sections for the Crashworthiness Design - Muthusamy, M Yoggaraj; Kamaruddin, Kamaruddin; Choiron, Moch. Agus (Jurnal Energi Dan Manufaktur, 2018)
In this study, crash behavior of optimization of initial folding square sections are evaluated. Three parameters of design are set as width (w), height (h) and thickness (t) with three levels. Deformation mode of crash box and energy absorbing due to frontal load is observed.  Response surface method is used to optimize the Initial folding square sections. Box-Bhenken is chosen to provide this setting and 13 models is built. Computer simulation is used to determine the energy absorption by using Software Finite Element Analysis. Based on computer simulation results, it can be denoted that w =1.1 mm, h = 0.9 mm and t = 2.75 mm produce the highest of energy absorption.